Design and Evaluation of an IoT-Based Monitoring and Biogas Distribution Control Prototype Using Palm Oil Mill Effluent - Rifki Rifki; Asminar Asminar; Abdul Djohar; Mustarum Musaruddin; Hasmina Tari Mokui; Adhi Setiawan Samsul (Jurusan Pendidikan Teknik Elektro, 2026)
Palm Oil Mill Effluent (POME) can be converted to biogas through anaerobic digestion; however, prototype-scale monitoring requires careful interpretation of low-cost sensor data. This study developed and performed a preliminary functional evaluation of an ESP32-based monitoring and biogas distribution control prototype using a 120-L digester charged with 50 L of POME and 50 L of water for four weeks. Five-point comparisons yielded mean absolute errors of 1.10 °C for the DS18B20 temperature sensor, 0.10 bar for the WPT83-G pressure sensor, and 0.132 V for the PZEM-004T voltage channel, respectively. The Blynk dashboard was programmed to update every 2 s, which was not a network latency measurement. Digester MQ-4 nominal readings increased from 0-351 in week 1 to 1,988-3,420 in week 4, while gas-bag readings reached 450-750. Because the MQ-4 sensor was not calibrated with certified methane mixtures, these values are relative gas-sensitive readings rather than validated methane concentrations. Both solenoid valves followed four commanded on/off states. Therefore, the prototype demonstrates proof-of-concept functional integration of sensing, visualization, and valve actuation, while gas composition, gas volume, network reliability, and generator performance require further validation.